2018
DOI: 10.12998/wjcc.v6.i15.944
|View full text |Cite
|
Sign up to set email alerts
|

Association between functional abdominal pain disorders and asthma in adolescents: A cross-sectional study

Abstract: AIMTo find the association between asthma and different types of functional abdominal pain disorders (FAPDs) among teenagers.METHODA cross-sectional study was conducted among 13 to 15-year-old children from six randomly selected schools in Anuradhapura district of Sri Lanka. Data were collected using translated and validated self-administered questionnaires (Rome III questionnaire, International Study on Asthma and Allergies in Childhood questionnaire, and Pediatric Quality of Life Inventory 4.0) and administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…When assessing Rome III-defined abdominal pain at 16y, early childhood asthma did not remain associated to AP-FGIDs, whereas asthma at 12y and 16y did. In accordance, the majority of the previous studies including children [ 16 , 17 , 20 25 ] report a high prevalence and/or increased risk for abdominal pain of functional origin [ 20 , 22 ], AP-FGIDs [ 21 , 23 ], and IBS [ 16 , 17 , 25 ] when asthma was present. Most studies, however, were cross-sectional [ 20 24 ] and of them only Kumari and Colman [ 21 , 23 ] used the Rome III criteria to define AP-FGIDs (none used the Rome IV criteria).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…When assessing Rome III-defined abdominal pain at 16y, early childhood asthma did not remain associated to AP-FGIDs, whereas asthma at 12y and 16y did. In accordance, the majority of the previous studies including children [ 16 , 17 , 20 25 ] report a high prevalence and/or increased risk for abdominal pain of functional origin [ 20 , 22 ], AP-FGIDs [ 21 , 23 ], and IBS [ 16 , 17 , 25 ] when asthma was present. Most studies, however, were cross-sectional [ 20 24 ] and of them only Kumari and Colman [ 21 , 23 ] used the Rome III criteria to define AP-FGIDs (none used the Rome IV criteria).…”
Section: Discussionsupporting
confidence: 81%
“…In accordance, the majority of the previous studies including children [ 16 , 17 , 20 25 ] report a high prevalence and/or increased risk for abdominal pain of functional origin [ 20 , 22 ], AP-FGIDs [ 21 , 23 ], and IBS [ 16 , 17 , 25 ] when asthma was present. Most studies, however, were cross-sectional [ 20 24 ] and of them only Kumari and Colman [ 21 , 23 ] used the Rome III criteria to define AP-FGIDs (none used the Rome IV criteria). Kumari et al showed an increased risk for concurrent FD, FAP, and abdominal migraine, but not IBS in asthmatics in a population-based sample of 1101 children in Sri Lanka [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…FD and functional abdominal pain have been associated with asthma in adolescents [ 58 ]. Likewise, asthma and food allergy, allergic rhinitis, and eczema have been associated with FAPDs in adults [ 59 , 60 , 61 , 62 , 63 , 64 ]. In an extensive primary care study, both FD and IBS were associated with allergic conditions, and the relationship was partially explained by a common association with anxiety and depression [ 63 ].…”
Section: Allergy and Functional Abdominal Pain Disordersmentioning
confidence: 99%